2014
DOI: 10.1152/ajpcell.00318.2013
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic adhesion of eryptotic erythrocytes to immobilized platelets via platelet phosphatidylserine receptors

Abstract: Glucose depletion of erythrocytes triggers suicidal erythrocyte death or eryptosis, which leads to cell membrane scrambling with phosphatidylserine exposure at the cell surface. Eryptotic erythrocytes adhere to endothelial cells by a mechanism involving phosphatidylserine at the erythrocyte surface and CXCL16 as well as CD36 at the endothelial cell membrane. Nothing has hitherto been known about an interaction between eryptotic erythrocytes and platelets, the decisive cells in primary hemostasis and major play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 59 publications
3
30
0
4
Order By: Relevance
“…An example of this is thromboxane, which was found to stimulate RBCs by inducing PS exposure on their surfaces, followed by an increase in cytosolic calcium content [76]. These responses have been found to be associated with reduced membrane deformability, increased adhesion, formation of pathomorphologies and a precursor to eryptosis [91][92][93]. The PS exposure further increases the adherence of RBCs to platelets and induces thrombosis [93].…”
Section: Rbc and Platelet Interactions In Ramentioning
confidence: 99%
See 2 more Smart Citations
“…An example of this is thromboxane, which was found to stimulate RBCs by inducing PS exposure on their surfaces, followed by an increase in cytosolic calcium content [76]. These responses have been found to be associated with reduced membrane deformability, increased adhesion, formation of pathomorphologies and a precursor to eryptosis [91][92][93]. The PS exposure further increases the adherence of RBCs to platelets and induces thrombosis [93].…”
Section: Rbc and Platelet Interactions In Ramentioning
confidence: 99%
“…These responses have been found to be associated with reduced membrane deformability, increased adhesion, formation of pathomorphologies and a precursor to eryptosis [91][92][93]. The PS exposure further increases the adherence of RBCs to platelets and induces thrombosis [93]. It is hence likely that structural variants and adhesive associations observable within the RA RBC pool could also be a result of this interaction-based effect.…”
Section: Rbc and Platelet Interactions In Ramentioning
confidence: 99%
See 1 more Smart Citation
“…The agglutination of RBCs at the site of plaque injury probably depends on platelet aggregation. Indeed, Walker and colleagues recently showed that senescent erythrocytes could stick to immobilized platelets, via the platelet phosphatidyl receptors, CXCL16 and CD36 [18]. Thereafter, ulcerated plaques are healed by migration and proliferation of local VSMCs that accumulate at the rupture site.…”
Section: Introduction: Phylogeny Of the Arterial System And Teleonomimentioning
confidence: 99%
“…However, the main signaling pathway documented as inducer of eryptosis is increase of cytosolic Ca 2+ activity ([Ca 2+ ] i )16. Calcium can directly cause the phosphatidylserine membrane translocation (cell scrambling)34. Moreover, calcium can activate K + channels with an efflux of KCl from the cell causing cell shrinkage35.…”
Section: Discussionmentioning
confidence: 99%